Solve the equation (2 – 5x) + (1 – 7x) = 1.​

Question

Solve the equation (2 – 5x) + (1 – 7x) = 1.​

in progress 0
Clara 3 days 2021-09-14T20:10:04+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-09-14T20:11:15+00:00

    Step-by-step explanation:

    2 - 5x + 1 - 7x - 1 = 0 \\ 2 - 12x = 0

    2 = 12x \\  \frac{2}{12}  = x

     \frac{1}{6}  = x

    0
    2021-09-14T20:11:55+00:00

    Step-by-step explanation:

    (2-5x ) + (1-7x) =1

    2-5x +1 -7x =1

    -12x + 3 =1

    -12x = -2

    therefore,

    X = -2/-12

    X = 1/11

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )